Adoption of cognitive-affective framework: case study of cosmetic e-commerce web sites / Norazimah Abd Jalil - Abd Jalil, Norazimah (2011)
Nowadays electronic commerce (e-commerce) web site is the main platform for company to do business. The e-commerce environment today, however, is much different than in the early days. As competition grows for online customers, companies cannot simply assume that if they build Web sites customers will come. There are studies begin to show that aesthetics elements such as color, graphics and music can play an important role in enhancing usage and enjoyment of information system. Objective of this research is to explore the aesthetics element that related to web site design and secondly is to evaluate user perception towards cosmetic e-commerce web site based on cognitive-affective framework. This research using questionnaire as an research instrument. The Statistical Package for Social Science (SPSS) version 15.0 is used as the analysis to analyse the data using Exploratory Factor Analysis (EFA), Confirmatory factor analysis (CFA) and independent T-Test. Findings from this research provide support of feedback from the actual user' opinion regarding current cosmetic e commerce web site. This result can help the developer identifying what is the item need to be improved in future development. Second, These research finding is highly relevant to developer that it is necessary to have a better process of evaluation before developing any cosmetic e-commerce web site.